Orofacial pain of muscular origin is not associated with herpes virus-6 infection: A pilot study - Shoji, Y.; Choo, H.L.; Leong, C.O.; Oo, A.L.; Townsend, G. (2014)
Aims: To carry out a pilot study to test the hypothesis that human herpes virus-6 (HHV-6) infection or reactivation plays a role in the pathogenesis of temporomandibular disorders (TMD) of muscular origin (ie, localized myalgia). Methods: Sixteen patients with localized myalgia participated in this pilot study. Thirty-six healthy individuals served as controls. The participants were examined clinically for the presence of the TMD according to the Research Diagnostic Criteria for TMD, and the salivary levels of HHV-6 were measured by quantitative polymerase chain reaction (qPCR). The Z test, Student t test, and Mann-Whitney U test were used as appropriate. Results: The results demonstrated that 77.8% of healthy individuals were HHV-6 positive, but a significantly lower proportion (43.8%) of the TMD patients with localized myalgia were positive for HHV-6 (P < .05, Fisher exact test). The levels of HHV-6B DNA were lower in the saliva of HHV-6 positive TMD patients with localized myalgia (median: 564 genome/mL; range: 184 to 5,835 genome/mL) than in that of healthy individuals (median: 1,081 genome/mL; range: 193 to 8,807 genome/mL), but the difference was not statistically significant (P > .05, Mann-Whitney U test). Conclusion: The results of this pilot study indicate that HHV-6 infection or reactivation does not appear to play a role in the pathogenesis of TMD reflecting a localized myalgia.